Characteristics of a Streptomyces coelicolor A3(2) Extracellular Protein Targeting Chitin and Chitosan - Saito, Akihiro (American Society for Microbiology, 2001)
Upstream of the Streptomyces coelicolor A3(2) chitinase G gene, a small gene (named chb3) is located whose deduced product shares 37% identical amino acids with the previously described CHB1 protein from Streptomyces olivaceoviridis. The chb3 gene and its upstream region were cloned in a multicopy vector and transformed into the plasmid-free Streptomyces lividans TK21 strain. The CHB3 protein (14.9 kDa) was secreted by the S. lividans TK21 transformant during growth in the presence of glucose, N-acetylglucosamine, yeast extract, and chitin. The protein was purified to homogeneity using anionic exchange, hydrophobic interaction chromatographies, and gel filtration. In contrast to CHB1, CHB3 targets α-chitin, β-chitin, and chitosan at pH 6.0 but does so relatively loosely. The ecological implications of the divergence of substrate specificity of various types of chitin-binding proteins are described.